Pencegahan dan Penanganan Kekerasan Seksual Berdasarkan Undang-Undang Nomor 12 Tahun 2022 di Desa Perkebunan Labuhan Haji - Pakpahan, Zainal Abidin; Risdalina, Risdalina; M, Indra Kumalasari; Hakim, Abdul; Siahaan, Nimrot (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
The term "violence" refers to actions that are forceful, ruthless, or cruel, whether physically, psychologically, economically, through threats, or as sexual violence, often based on gender. Sexual violence frequently occurs due to inherent desires and various factors that trigger such behavior. The impact is not only on the direct victims but also on children, who can become victims or perpetrators. Law Number 12 of 2022 on the Prevention and Handling of Sexual Violence aims to address and prevent sexual violence, particularly against women and children. In Desa Perkebunan Labuhan Haji, a socialization event was held on June 13, 2024, attended by 30 participants, including the Village Head, village officials, neighborhood officials, religious leaders, community leaders, and students. The outcome of this event demonstrated that the community increasingly understands the importance of preventing sexual violence and its legal consequences. Early prevention efforts are crucial to avoid sexual violence and ensure that perpetrators are penalized according to the applicable regulations.